Has Winter Weather in Southwest Ohio Been Affected by the El Niño Southern Oscillation, the North Atlantic Oscillation, the Pacific Decadal Oscillation, and the Atlantic Multidecadal Oscillation? - Blue, John A. (CORE Scholar, 2022)
Winter temperature and precipitation in Southwest Ohio over the last century were examined for anomalies attributable to teleconnections with large-scale atmospheric perturbations caused by the El Niño Southern Oscillation (ENSO), the North Atlantic Oscillation (NAO), the Pacific Decadal Oscillation (PDO), and the Atlantic Multidecadal Oscillation (AMO). The record of temperature gives evidence of a teleconnection with the NAO, ENSO, and PDO, with the strongest link being for phases of the NAO. Most winters during positive NAO phases had mean monthly temperature warmer than the century long mean, and the majority of negative NAO phase winters had colder temperatures. The difference in average temperature between positive and negative NAO phase winters was 0.82°C and is statistically significant at the p=0.0005 level. Winters were also increasingly warmer when NAO was increasingly positive, and increasingly colder when NAO was increasingly negative (regression-model with p=E-5). The support for this teleconnection was the strongest when NAO is out of phase with ENSO and PDO. For example, the 21 winters when the NAO phase was positive and ENSO and PDO phases were negative (condition A) were 1.73°C warmer on average than the 12 winters when NAO was negative and ENSO and PDO were positive (condition B), and the difference is statistically significantly different at the p=0.02 level. The warmest winters on record (mean-monthly temperature of 6.9°C) occurred under condition A, while the coldest (5.2°C) occurred under condition B. The NAO, ENSO and PDO variations explain 0.25 of the overall variance in mean winter temperature (multi-regression-model with p=3.5E-05). The record does not give statistical support for an influence on winter temperature by the AMO. The record gives statistical support for a smaller influence of NAO, ENSO, PDO, and AMO phases on precipitation, with the phases explaining 7% of the variance in winter precipitation (multi-regression model with p=0.018).